Going Ape: Animacy and affect in Rise of the Planet of the Apes (2011). Issue 2 (3rd April 2019) - West, Thomas J.
ABSTRACT: When it was released in 2011, few thought that the film Rise of the Planet of the Apes would be a success. To the surprise of many, however, Rupert Wyatt's take on the mythology garnered both box office success and critical praise. Most critics agreed that Caesar, more than any of the film's human characters, stood as the star of the film. This character drew viewers into a sometimes uncomfortable and disconcerting identification with a non-human protagonist. Such a critical response points to the film's critique of what Mel Y. Chen has referred to as the hierarchy of animacy, which enables humanity to both classify and oppress nonhuman animals and, simultaneously, privileges and reinforces the centrality of human subjectivity. However, Rise of the Planet of the Apes challenges this hierarchy in part by encouraging spectators to affectively identify with Caesar as he develops his revolutionary consciousness. Further, by showcasing Caesar's linguistic ability and his self-actualization, and through its utilization of motion capture technology as opposed to live apes, the film critiques the artificial limitations imposed by the animacy hierarchy and explores the possibilities of thinking beyond the human.